CORPORATE ENVIRONMENTAL PERFORMANCE AND CORPORATE FINANCIAL PERFORMANCE: A CONCEPTUAL PAPER - Qichun Wu; Fumitaka Furuoka, (Malaysian Journal of Business and Economics (MJBE), 2020)
There is an ongoing debate on the relationship between corporate environmental performance (CEP) and corporate financial performance (CFP). This conceptual paper aims to contribute to the existing literature by integrating previous research on the CEP-CFP relationship and identifying the moderating effect of firm size on the relationship between these variables. It also proposes a new conceptual framework in which the positive relationship between the CEP and the CFP would be moderated by the firm size.